Sizing and Dyeing Property Improvement of Cotton Fabric Treated with Corona Discharge - Ma, Pibo (Asian Journal of Chemistry, 2012)
In this study, corona discharge treatment is applied to cotton fabric at various discharge voltages and time. Scanning electron microscopic graphs show that the surface of cotton fiber is etched with obvious ridge, uneven and rough trenched structure. The breaking strength and hydrophilic properties of treated cotton fabric are improved evidently after the corona discharge treatment. Surface affinity between the treated fabric surface and the starch sizing is increased at the same time and the dye uptake of treated fabric was increased when the applied voltage and treating time increased. Its effects on surface modification of cotton fabric and its application in finishing are investigated with a range of analytical methods. The results suggest that corona discharge can be successfully applied the finishing of cotton fabric, especially in the green processing of sizing and dyeing.